Retrospective Observational Study on Rebamipide Ophthalmic Suspension on Quality of Life of Dry Eye Disease Patients - Yuri Sakane; Masahiko Yamaguchi; Atsushi Shiraishi (Journal of Ophthalmology)
Purpose. The Dry Eye-Related Quality-of-Life Score (DEQS) is a Japanese dry eye-specific questionnaire that has been used to assess the symptoms of dry eye and their effects on the quality of life (QOL) in Japanese individuals. The purpose of this study was to determine the effect of rebamipide (RBM) on the QOL of Japanese patients with dry eye disease (DED). Method. The medical records of 43 patients (3 men and 40 women; mean age: 64 ± 14 years; range: 32 to 83 years), who were diagnosed with DED and treated with RBM at the Ehime University Hospital between November 2012 and June 2016, were reviewed. The effects of 2% rebamipide (RBM) ophthalmic suspension on the symptoms of DED was determined by the answers to the DEQS questionnaire and clinical findings. The clinical findings before and 1, 3, 6, 12, and 24 months after initiating the RBM treatment were reviewed. The following data were collected from the DEQS: the Summary score and two subscale scores, the Bothersome ocular symptoms score, and the Impact on daily life score. In addition, the standard fluorescein staining score, the Schirmer I test score, and the tear breakup time (TBUT) score were analyzed. Result. The Summary score and Impact of daily life score of the DEQS were improved significantly after 1, 3, 6, and 12 months of RBM, and the Bothersome ocular symptoms scores of the DEQS were also improved after 1, 3, and 6 months. The fluorescein staining scores were significantly decreased after 1, 3, 6, and 12 months, and the TBUT score was significantly increased after 1 month. Conclusion. RBM treatment improves the QOL by alleviating the corneal and conjunctival epithelial damages. The DEQS is a useful questionnaire that can assess the severity of the DED symptoms and their impact on the QOL. This trial is registered with UMIN000024405.